Capacitor electrical discharge consolidation of metallic powders—a review - Aranda, RM; Ternero, F; Lozano-Pérez, S; Montes, JM; Cuevas, FG (MDPI, 2021)
Manufacturing metallic materials from elemental or alloyed powders is an option in many industrial processes. Nevertheless, the traditional powder metallurgy processing including furnace sintering is at times detrimental for the microstructure attained in the powders. Alternative sintering processes based on the use of electricity and the energy obtained by the Joule effect in powder particles can be quick enough to avoid microstructural changes. In particular, when the energy is stored in a capacitor and then discharged, the heating process is extremely quick, lasting milliseconds or even microseconds. This process, generally known as electrical discharge consolidation, has been applied to a wide variety of metallic materials, easily preserving the original microstructure of the powders. Both porous or homogeneous and highly densified material can be obtained, and without losing the desired properties of the consolidated material. A general overview of the process and applications, as well as the results obtained by different research groups around the world, have been reviewed in this manuscript.